2021
DOI: 10.3390/su132112288
|View full text |Cite
|
Sign up to set email alerts
|

Towards More Sustainable Diets: Investigating Consumer Motivations towards the Purchase of Green Food

Abstract: The concept of green consumption has become an environmental topic that draws worldwide attention. In order to mitigate environmental damage, it is imperative to increase the recyclability of the food system, and therefore, novel, sustainable, and produced foods need to be supplied to the food system. Among such foods, precooked plant-based foods (PPBFs), which feature health, convenience, and functionality, have become a new trend of the food culture. This study uses the value–attitude–behavior (VAB) model as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…(2) This study analyzes the dynamic evolution characteristics of the diffusion of unethical behavior among green food enterprise, thus making the research conclusion realistic. (3) This study provides novel conclusions that have theoretical and practical application value: single adjustment of the level of enterprise moral clarity, damage degree of unethical behavior, and enterprise influence can only reduce the diffusion probability of unethical behavior to a certain extent. Even if the formulation of control strategies is based on their interaction, the diffusion remains unable to disappear.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…(2) This study analyzes the dynamic evolution characteristics of the diffusion of unethical behavior among green food enterprise, thus making the research conclusion realistic. (3) This study provides novel conclusions that have theoretical and practical application value: single adjustment of the level of enterprise moral clarity, damage degree of unethical behavior, and enterprise influence can only reduce the diffusion probability of unethical behavior to a certain extent. Even if the formulation of control strategies is based on their interaction, the diffusion remains unable to disappear.…”
Section: Introductionmentioning
confidence: 90%
“…Moral and ethical issues of green food enterprises are transcending the traditional research category of philosophy, and unethical behavior has gradually become a common concern in the field of enterprise management theory and practice [1,2]. With the continuous development of green food, green food safety has gradually become the focus of attention [3][4][5][6]. Green food enterprise refers to enterprises in accordance with the scientific method to produce and process pollution-free safe, high-quality and nutritious foods.…”
Section: Introductionmentioning
confidence: 99%
“…Its versatility is evident across various domains, including contexts centered around environmental and ethical considerations (Kim & Hall, 2021). Within the domain of food consumption, the VAB model has been proven to be indispensable in comprehending consumer attitudes and behaviors concerning green foods (Chang et al, 2021), seaweed food products (Govaerts & Olsen, 2022), online food buying (Yan et al, 2022) and sustainable consumption (Chang et al, 2021; Kim et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…After attitude, environmental concern seems to be another factor determining green food purchase intention. According to Chang et al (2021), environmental concern leads to the intention to purchase pre-cooked plant-based food. Similarly, the results of Shen and Chen's (2020) study revealed environmental concern is significantly associated with the purchase intention of meat alternatives.…”
Section: Intrapersonal Dimensionmentioning
confidence: 99%